Collagen Growth Pattern in Human Articular Cartilage of the Knee. (December 2021) - Jørgensen, Adam E.M.; Schjerling, Peter; Krogsgaard, Michael R.; Petersen, Michael M.; Olsen, Jesper; Kjær, Michael; Heinemeier, Katja M.
Objective: During skeletal growth, the articular cartilage expands to maintain its cover of bones in joints, however, it is unclear when and how cartilage grows. We aim to determine the expanding growth pattern and timing across the tibia plateau in human knees. Design: Six human tibia plateaus (2 healthy, 2 with osteoarthritis, and 2 with posttraumatic osteoarthritis) were used for full-depth cartilage sampling systematically across the joint surface at 12 medial and 4 lateral sites. Methodologically, we took advantage of the performed nuclear bomb tests in the years 1955 to 1963, which increased the atmospheric 14 C that was incorporated into human tissues. Cartilage was treated enzymatically to extract collagen, analyzed for 14 C content, and year at formation was determined from historical atmospheric 14 C concentrations. Results: By age-determination, each tibia condyle had central points of formation surrounded by later-formed cartilage toward the periphery. Furthermore, the tibia plateaus contained collagen with 14 C levels corresponding to mean donor age of 11.7 years (±3.8 SD). Finally, the medial condyle had lower 14 C levels corresponding to formation 1 year later than the lateral condyle ( P = 0.009). Conclusions: Human cartilage on the tibia plateau contains collagen that has experienced little if any turnover since school-age. The cartilage formation develops from 2 condyle centers and radially outward with the medial condyle finishing slightly later than the lateral condyle. This suggests a childhood programmed cartilage formation with a very limited adulthood collagen turnover.